1977
DOI: 10.1210/endo-100-1-39
|View full text |Cite
|
Sign up to set email alerts
|

The Culture of Pig Oocytes in Minimal Medium, and the Influence of Progesterone and Estradiol-17β on Meiotic Maturation

Abstract: Pig oocytes, with (intact) or without (denuded) adhering granulosa cells, were cultured for 33 to 35 h in minimal culture media containing bovine serum albumin and either progesterone or estradiol-17beta or both steroids. The incidence of maturation for intact oocytes in minimal medium was comparable, if not superior, to that observed by other investigators using complex culture media. No statistically significant stimulation of maturation by progesterone was observed for either intact or denuded oocytes. Estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1
1

Year Published

1978
1978
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(38 citation statements)
references
References 0 publications
2
34
1
1
Order By: Relevance
“…Progesterone (31-8 µ ) has also been found not to affect maturation of corona-enclosed human (Shea, Baker & Latour, 1975) or denuded porcine (McGaughey, 1977) oocytes in culture. It may, in addition, reverse the inhibition of porcine oocyte maturation caused by oestradiol-17ß (McGaughey, 1977). On the other hand, progesterone (10 and 31-8 µ ) has been shown to decrease maturation frequency of denuded mouse (Nekola & Smith, 1974;Eppig & Koide, 1978) and corona-enclosed rabbit oocytes (Smith, Tyler & Erickson, 1978).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Progesterone (31-8 µ ) has also been found not to affect maturation of corona-enclosed human (Shea, Baker & Latour, 1975) or denuded porcine (McGaughey, 1977) oocytes in culture. It may, in addition, reverse the inhibition of porcine oocyte maturation caused by oestradiol-17ß (McGaughey, 1977). On the other hand, progesterone (10 and 31-8 µ ) has been shown to decrease maturation frequency of denuded mouse (Nekola & Smith, 1974;Eppig & Koide, 1978) and corona-enclosed rabbit oocytes (Smith, Tyler & Erickson, 1978).…”
Section: Introductionmentioning
confidence: 98%
“…Oestradiol-17ß (176-2 µ ) reduced significantly the incidence of maturation of cumulus-enclosed rabbit and bovine oocytes (Robertson & Baker, 1969), denuded porcine oocytes at concentrations of 3-67 and 36-7 µ (McGaughey, 1977) and denuded mouse oocytes at a concentration of 100 µ (Nekola & Smith, 1974) and 36-7 µ (Eppig & Koide, 1978). Progesterone (102 µ ) has been reported to enhance the maturation of denuded bovine and rabbit (Robertson & Baker, 1969), cumulus-enclosed rabbit (Bae & Foote, 1975) and denuded oocytes from gonadotrophin-treated prepubertal rhesus monkeys (Gould & Graham, 1976).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicting results have been reported on the effect of progesterone : either there was a lower incidence of maturation in denuded mouse oocytes (Eppig and Koide, 1978) and of corona enclosed rabbit oocytes (Smith et al, 1978), or an enhancement of nuclear maturation of cumulus enclosed rabbit oocytes (Bae and Foote, 1975). A negative effect on pig oocytes of oestradiol (McGaughey, 1977) and androgens (Rice and Me Gaughey, 1981), has been described in in vitro studies. Similarly Daniel et al (1986) concluded that testosterone and 19nor-testosterone inhibit porcine oocyte nuclear maturation ; however this effect is only observed after 12 h of culture but neither at 6 h nor at 24 h. (rat, Liberman et al, 1976 ;Billig et al, 1983).…”
mentioning
confidence: 98%
“…In 1940, it was shown that either diethylstilbestrol (DES) or estradiol-17/3 markedly stimulated granulosa cell proliferation and also increased ovarian responsiveness to gonadotropins in the immature hypophysectomized rat (61,62). The effects of estrogen and progesterone upon ovum maturation in vitro provide another possible example(s) of steroid mediated intra-ovarian regulation (63).…”
Section: Intra-ovarian Regulationmentioning
confidence: 99%